Development of Physics Teaching Materials Based on Concept Elaboration to Enhance Students’ Critical Thinking Skills - Uranti Amba Lembang; Muhammad Arsyad; Helmi (Postgraduate, University of Mataram, 2025)
This study aims to develop concept elaboration-based physics teaching materials to enhance students' critical thinking skills. The development utilized a 4D (define, design, develop, disseminate) model, which involved validation by experts, practicality assessment by teachers, and field testing with thirty-two Grade XI students. The teaching materials were evaluated for validity, practicality, and effectiveness. The content validity analysis using Aiken's V produced values ranging from 0.77 to 0.82, conveying that the teaching materials were in the valid category. Teachers' assessments showed high practicality, with an average score of 81.5%, while students provided good responses to the teaching materials, with an average of 81%. The effectiveness test, using the Mann–Whitney U test, showed a significant difference between the experimental and control classes (Z = 3.6 > 1.96), with average critical thinking scores of 21 and 17 in the post-test, respectively. These results demonstrate that the concept elaboration-based teaching materials are valid, practical, and effective in improving students' critical thinking skills. The implementation of this approach is expected to enhance students' critical thinking skills within the physics learning experience.